A Culture of Flourishing: A Feminist Ethical Framework for Incorporating Child Sexual Abuse Prevention in Catholic Institutions - Moles, Katia (Journal of feminist studies in religion, 2020)
In the wake of the 2002 Boston Globe coverage of the child sexual abuse (CSA) scandal at the hands of Catholic clergy, the U.S. Conference of Catholic Bishops responded by requiring adults working in Catholic institutions to take CSA prevention training, and recommended such training for youth. Such measures profess institutional commitment to change. However, the current approach to young people's sexuality, which is narrowly focused on protection and restriction, undermines the magisterium's professed commitments to holistic education and human flourishing. In order to fulfill these commitments, Katia Moles suggests that U.S. Catholic institutions cultivate a culture of sexual flourishing in which CSA prevention is part of lifelong comprehensive sexuality education and children are recognized as moral agents. Drawing on Catholic feminist sexual ethics, Moles proposes normative criteria for a developmental sexual ethic conducive to such a culture. Empirical evidence indicates U.S. Catholics are ready for a renewed sexual ethics. Finally, she discusses how children could inform Catholic sexual theology.